EVALUATION ANALYSIS OF CONTROL LOOP FEEDBACK SYSTEMS IN RESONANT NETWORK OF THE ISOLATED DC-DC CONVERTER DESIGN - ROPLI, EMY AZLIZA (Universiti Teknologi Petronas, 2006)
The existing output of the isolated DC-DC Converter requires a good switching device and needs to be controlled in order to achieve the desired output voltage with less output ripple voltage. However, this converter cannot maintain the output voltage with good efficiency in high power application. Currently, any semiconductor devices need greater efficiency in switching such as high power switching power supply, motor drives for electrical vehicle (EV), communication systems and others. A new DC-DC Converter modified via resonant network and controlled with the application of controller and gate circuit is proposed. The PWM Controller technique is used to control the output voltage and duty cycle ofthe switches. The paper will cover studies onthe Zero-Current Switching circuit design and PWM controller in isolated DC-DC Converter. Then, the simulation using Cadence Pspice is carried out. The performance ofthe design will be evaluated based on parameters such as input ripple current, output ripple voltage and efficiency. A control loop feedback systems in resonant network of the FB-ZCS with better efficiency, less input ripple current of 1.94% and less output ripple voltage of0.47% are obtained from this project. But, the results obtained cannot be compared with the conventional scheme because of big differences and suggestions havebeenmade for the improvement.